The Innovation Imperative for Developing East Asia - Cirera, Xavier; Kuriakose, Smita; Mare, Davide S.; Mason, Andrew D.; Tran, Trang Thu; de Nicola, Francesca (World Bank, 2021)
After a half century of transformative economic progress that moved hundreds of millions of people out of poverty, countries in developing East Asia are facing an array of challenges to their future development. Slowed productivity growth, increased fragility of the global trading system, and rapid changes in technology are all threatening export-oriented, labor-intensive manufacturing—the region’s engine of growth. Significant global challenges—such as climate change and the COVID-19 pandemic—are exacerbating economic vulnerability. These developments raise questions about whether the region’s past model of development can continue to deliver rapid growth and poverty reduction. Against this background, The Innovation Imperative in Developing East Asia aims to deepen understanding of the role of innovation in future development. The report examines the state of innovation in the region and analyzes the main constraints that firms and countries face to innovating. It assesses current policies and institutions, and lays out an agenda for action to spur more innovation-led growth. A key finding of the report is that countries’ current innovation policies are not aligned with their capabilities and needs. Policies need to strengthen the capacity of firms to innovate and support technological diffusion rather than just invention. Policy makers also need to eliminate policy biases against innovation in services, a sector that is growing in economic importance. Moreover, countries need to strengthen key complementary factors for innovation, including firms’ managerial quality, workers’ skills, and finance for innovation. Countries in developing East Asia would also do well to deepen their tradition of international openness, which could foster openness in other parts of the world. Doing so would help sustain the flows of ideas, trade, investment, and people that facilitate the creation and diffusion of knowledge for innovation
Cambodia
China
East Asia
East Asia and Pacific
Indonesia
Keywords: ECONOMIC GROWTH; GROWTH DRIVERS; INNOVATION; INNOVATION POLICY; INTERNATIONAL TRADE; LABOR SKILLS; MANAGERIAL CAPABILITIES; POVERTY REDUCTION; PRIVATE SECTOR DEVELOPMENT; PRODUCTIVITY GROWTH; RISK FINANCE; SERVICES TRADE; TECHNOLOGY ADOPTION; TECHNOLOGY CHANGE; TECHNOLOGY DIFFUSION; TECHNOLOGY INNOVATION; TECHNOLOGY TRANSFER